Necrotic Liver Lesion Resolution: Another Mode of Liver Regeneration - Chen, Cheng; Feng, Dechun; Wang, Yang; Yao, Tiantian; Mackowiak, Bryan; Gao, Bin (Seminars in Liver Disease, 2024)
The liver has the great ability to regenerate after partial resection or injury, and the mechanisms underlying liver regeneration have been extensively investigated. Interestingly, acute liver injuries triggered by various etiologies are associated with the formation of necrotic lesions, and such necrotic lesions are also rapidly resolved. However, how necrotic liver lesions are repaired has not been carefully investigated until recently. In this review, we briefly summarize the spatiotemporal process of necrotic liver lesion resolution in several liver injury models including immune-mediated liver injury and drug-induced liver injury. The roles of liver nonparenchymal cells and infiltrating immune cells in controlling necrotic liver lesion resolution are discussed, which may help identify potential therapies for acute liver injury and failure.
Keywords: liver necrotic lesion; acute liver injury; macrophages; concanavalin A (ConA); acetaminophen (APAP)